2017
DOI: 10.3892/etm.2017.4019
|View full text |Cite
|
Sign up to set email alerts
|

VEGF treatment promotes bone marrow-derived CXCR4+ mesenchymal stromal stem cell differentiation into vessel endothelial cells

Abstract: Stem/progenitor cells serve an important role in the process of blood vessel repair. However, the mechanism of vascular repair mediated by C-X-C chemokine receptor type 4-positive (CXCR4+) bone marrow-derived mesenchymal stem cells (BMSCs) following myocardial infarction remains unclear. The aim of the present study was to investigate the effects of vascular endothelial growth factor (VEGF) on vessel endothelial differentiation from BMSCs. CXCR4+ BMSCs were isolated from the femoral bone marrow of 2-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…More and more evidences show that BMSCs could directly differentiate into vascular endothelial cells and smooth muscle cells, even forming functional vessels [ 15 , 60 ]. However, reports suggest that differentiation either by transdifferentiation or cell fusion appears too low to explain the significant improvement of vascular repair [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more evidences show that BMSCs could directly differentiate into vascular endothelial cells and smooth muscle cells, even forming functional vessels [ 15 , 60 ]. However, reports suggest that differentiation either by transdifferentiation or cell fusion appears too low to explain the significant improvement of vascular repair [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs orchestrate the repair process of injured vessels by various mechanisms such as transdifferentiation, microvesicles or exosomes, and secreting cytokines [ 13 , 14 ]. MSCs can directly differentiate into endothelial cells to participate in angiogenesis [ 15 ] or migrate and home to the injured large blood vessel for vascular repair by regulating various cell cytokines, such as transforming growth factor beta (TGF- β ), vascular endothelial growth factor (VEGF), and intercellular cell adhesion molecules (ICAM) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that obesity, insulin resistance, and type 2 diabetes are associated with abnormal endothelial function and participate in the occurrence and development of diabetes mellitus and small vascular complications [8]. Vascular endothelial growth factor (VEGF) is a crucial cytokine used to promote the formation of new blood vessels, which may promote vascular endothelial cells, smooth muscle cell mitosis, vascular permeability, and angiogenesis [9, 10]. Previous studies on the association between VEGF and vascular disease revealed that serum VEGF was significantly increased in patients with diabetes mellitus, and the increase of VEGF was closely associated with the germination of diabetic angiopathy [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy significantly increased vascular density, decreased the formation of scar tissue, and improved cardiac function compared to either treatment alone or to untreated infarcted control rats [ 40 ]. VEGF treatment also promoted the differentiation of CXCR4-positive BMSCs into vessel endothelial cells in vitro [ 41 ]. Another research study has suggested that overexpression of the cellular repressor of adenovirus E1A-stimulated genes in BMSCs may promote VEGF-induced angiogenesis by inhibiting Von Hippel-Lindau tumor suppressor-mediated HIF-1α degradation, consequently protecting against rat MI [ 42 ].…”
Section: The Role Of Bmscs In Angiogenesismentioning
confidence: 99%